Fabrication of water filter using silica powder from rice husk waste product under compaction method - Muslem, Muhammad Firdaus; Ahmad, Sufizar; Isamudin, Ikhwan; Abd Rahman, Hamimah; Mahzan, Shahruddin; Azmi, Mohd Azham; Ismail, Azzura; Sufi, Syahmie (2024)
Ceramic water filtration is the method of filtering water using a porous ceramic medium to remove contaminants or germs and also the pore size of the ceramic water filter is small enough to catch anything larger than a water molecule, including bacteria. By producing silica water filter from rice husk for the use in water filter can help to purify the water and remove unwanted substance from the water. This study, the type of silica which is amorphous is used with very low residual carbon content was successfully achieved through combustion with a temperature of 500 oC. The sample of product was prepared and each of the sample product were mixture with Polyethylene Glycol by 1 wt%. The sample product was compacted by hydraulic press machine with the pressure used is 7 tones. The sintering process has been conducted in temperature of 900oC,950oC,1000oC,1050oC and 1100oC with two different composition of silica which is 60 wt% and 65 wt%. The result of bulk density, apparent porosity and water absorption were recorded for each sample. Based on the result, the favorable properties of sample sintering were obtained at sintering temperature of 1100oC Thus, the appropriate values of apparent porosity, water absorption, and bulk density for silica 60 wt% were 59.8499%, 71.2486%, and 0.84 g/cm3, respectively, while for silica 65 wt% were 65.5086%, 82.9045%, and 0.7902 g/cm3. In conclusion, the objective of this study was achieved to filter the waste water using silica water filter